Stabilizing and Tuning the Laser Frequencies in Er-Doped Fiber Ring Lasers Based on Microbubble Resonators - Haotian Wang; Xuliang Fan; Zihao Li; Ting Tang; Fan Wu; Deyuan Shen; Xiang Wu (IEEE Photonics Journal)
The laser frequency of an Er-doped fiber ring cavity is stabilized using the microbubble resonator (MBR) as the feedback element. The linewidth of the laser is nearly 86 MHz at ∼1560 nm measured by the Fabry–Perot interferometer. Since the thermooptic effect changes the reflectivity of the modes excited inside the MBR, the transition from the dual-wavelength operation to a stable single-wavelength output is found as increasing the pump power. The outstanding advantage of such laser is the microfluidic channel of the MBR which provides an excellent platform for the light to interact with the liquids. Thus, the laser wavelengths could be tuned by injecting different refractive index (RI) liquids into the microbubble. A coupled-cavities system is setup through inserting the MBR into the fiber cavity directly, of which the laser spectrum is very sensitive to the light polarization. Moreover, the laser wavelength could be tuned in a wide wavelength range if the thin-wall MBR is adopted. It provides a way to realize different lasing statues by controlling the light polarization or the RI of liquids inside the MBR.